2015
DOI: 10.5897/ajb2015.14956
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bioactive chemical components of two medicinal plants (Coriandrum sativum and Melia azedarach) leaves using gas chromatography-mass spectrometry (GC-MS)

Abstract: The main objective of this study was to determine the phytochemical composition in the leaves of Coriandrum sativum, using methanolic extraction and report the main functional components by using IR technique. The phytochemical compounds in the extract were then screened by GC-MS method. Seven bioactive phytochemical compounds were identified in the methanolic extract of C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…Some acid compounds also showed antimicrobial activity ( Himaman et al, 2016 ). Hexadecanoic acid,2- hydroxy-1-(hydroxymethyl) ethyl ester extracted from medicinal plants ( Melia azedarach leaves) had antioxidant, anti-inflammatory, and anthelmintic activities ( Ali et al, 2015 ). Thus, we speculated that these compounds play a key role in the broad-spectrum antifungal activity of Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…Some acid compounds also showed antimicrobial activity ( Himaman et al, 2016 ). Hexadecanoic acid,2- hydroxy-1-(hydroxymethyl) ethyl ester extracted from medicinal plants ( Melia azedarach leaves) had antioxidant, anti-inflammatory, and anthelmintic activities ( Ali et al, 2015 ). Thus, we speculated that these compounds play a key role in the broad-spectrum antifungal activity of Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have mentioned that camphor, spathulenol, and farnesol found in the composition of C. heyneana volatile oil have various pharmacological activities. Camphor may enhance the immune system, and spathulenol may have strong antioxidants and prevent inflammation, while farnesol may reduce oxidative stress and inflammation (18)(19)(20). Therefore, various chemical compounds in C. heyneana contribute in different ways to protect the liver from injury.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial number of active components were also separated and identified from different chinaberry parts, such as leaves, bark, fruit, and seeds. A substantial number of compounds extracted by methanol were found using GC-MS in chinaberry leaves, and the results demonstrated that the extracts contained trichloromethane, 2-pyrrolidinyl-methylamine, propanedioic acid, diethyl ester, and 2-piperidimethanamine, among others ( Al-Marzoqi et al 2015 ). The ethanol extracts of chinaberry leaves exhibited significant antimicrobial activity to several bacteria, including S. aureus .…”
Section: Discussionmentioning
confidence: 99%
“…The human pathogens Enterococcus faecalis, E. coli, P. aeruginosa and Klebsiella oxytoca were susceptible to extracts from chinaberry leaves, particularly the petroleum ether fraction that consists of secondary metabolites, such as alkaloids, terpenes/sterols, saponins, tannins and anthocyanins ( Rojas Sierra et al 2012 ). A variety of compounds have been found in the methanolic extracts from chinaberry, including propanedioic acid, butanedioic acid, diethyl ester, 2-pyrrolidinyl-methylamine, 2-piperidimethanamine, and trichloromethane ( Al-Marzoqi et al 2015 ). In addition, a substantial number of different ingredients were also isolated and identified from chinaberry by different research groups, which repeatedly demonstrated that the components of extracts varied with the extracted parts, solvents, and methodology.…”
Section: Introductionmentioning
confidence: 99%